Documenting the undocumented : latino/a narratives and social justice in the era of Operation Gatekeeper - Caminero-Santangelo, Marta, 1966- (University Press of Florida, 2016)
Looking at fiction and nonfiction by citizen journalists and undocumented writers, Caminero-Santangelo finds that latino/a writers increasingly express a sense of solidarity with undocumented immigrants. She also notes, however, that the literary and narrative response is far from heterogeneous.